Epidemiology, Diagnosis, and Management of Esophageal Adenocarcinoma - Rubenstein, Joel H. (Gastroenterology, 2015)
Esophageal adenocarcinoma (EAC) is rapidly increasing in incidence in Western cultures. Barrett’s esophagus (BE) is the presumed precursor lesion for this cancer. Several other risk factors for this cancer have been described, including chronic heartburn, tobacco use, Caucasian race, and obesity. Despite these known associations, most patients with EAC present with symptoms of dysphagia from late-stage tumors—only a small minority of patients are identified in screening and surveillance programs. Diagnostic analysis of EAC usually commences with upper endoscopy, followed by cross-sectional imaging. Endoscopic ultrasound is useful to assess local extent of disease as well as the involvement regional lymph nodes. T1a EAC may be treated endoscopically; some patients with T1b disease might also benefit from endoscopic therapy. Locally advanced disease is generally managed with esophagectomy, often accompanied by neoadjuvant chemoradiotherapy or chemotherapy. The prognosis is based on tumor stage: patients with T1a tumors have an excellent prognoses, whereas few patients with advanced disease have longterm survival.